Analisis Tingkat Kebisingan di Tempat Bermain Anak X Di Kota Palangka Raya - Yunita Enzelina Silaban; Akhmadi Surya Nata; Uci Purnama Purba; Reni Agustiani (Jurusan Fisika, Universitas Bangka Belitung, 2024)
Children's play areas that exceed the Noise Limit Value (NTV) can cause hearing health problems, including physiological and communication disorders. Therefore, this study aims to evaluate the noise level at one of the X children's playgrounds in Palangka Raya City which is busy with visitors. This research is important for playground owners to create a safe and comfortable environment for visitors. Noise levels are measured using a sound level meter which is then analyzed to determine the average noise value at each data collection point. Based on the analysis carried out, it shows that the average noise value at children's playground X in Palangka Raya City on weekdays is 79.52 dBA, while on holidays it reaches 81.76 dBA. This value exceeds the threshold recommended by the World Health Organization (WHO) and the Indonesian Ministry of Health for recreational areas which should be in the range of 70 dB. Based on this research, it is recommended that management take mitigation steps such as using building materials that absorb sound, limiting children's play time, and providing ear protection for zones with high noise levels.